Deflector; Efficiency; 180° Twist Angle; Savonius Turbine; Wind Energy; - Timotius Pabura; Ramli Ramli; Aslim Muda Aziz; M Ilham Nur; Risa B Umar; Haslinda (Journal Teknik Dan Teknologi, 2025)
Savonius wind turbines are a type of vertical axis wind turbine that is widely developed because it is able to operate at low wind speeds and has a simple construction. However, the performance of the Savonius turbine is relatively low due to the negative torque in the returning blade blade. One method that can be applied to improve turbine performance is the use of deflectors as wind flow directers. This study aims to analyze the effect of deflector angle variations on the performance of a two-blade twist type Savonius wind turbine with a twist angle of 180°. The research method used is an experimental method with testing using a wind tunnel. The variations of deflector angles used include no deflector, 30°, 45°, and 60°. The performance parameters analyzed include rotational speed, torque, turbine power, tip speed ratio, and turbine efficiency. The results of the study show that the addition of a deflector has a significant effect on improving turbine performance. The deflector angle of 60° delivers the best performance with the highest efficiency value compared to other variations. This is due to the ability of the deflector to direct the wind flow more optimally to the advancing blade blade and reduce the negative torque on the returning blade.